Growing Up Can Be Hard to Do: Reimagining 1 Structurally Supportive Pediatric-to-Adult Transitions of Care from a Rights-Based Perspective - Michelle Munyikwa; Charles K. Hammond; Leanne Langmaid; Leah Ratner (Harvard FXB Center for Health and Human Rights, 2023)
Extended life expectancies and shifting dynamics in chronic disease have changed the landscape of public health interventions worldwide, with an increasing emphasis on chronic care. As a result, transition from pediatric to adult care for medically complex adolescents and young adults is a growing area of intervention. Transition medicine is a nascent field whose current emphasis is on middle- and high-income countries, and thus far its methods and discourse have reflected those origins. Through several case-based examples, this paper aims to highlight the possibilities of an analytic approach grounded in structural competency for transforming transition medicine through a human rights-based framework, with an emphasis on imagining a more global framework for transition medicine. Our cases highlight the disparities between patients navigating pediatric to adult-based care, illuminating social stigma, stratification between public and private insurances, engagement in risk-taking behaviors, family conflict, and challenges with transition readiness. To reimagine transition medicine so that it is based on human rights, we must prioritize structural solutions that embrace multisectoral integration and holistic mental health support rather than oppress and marginalize these critical systemic adaptations. We aim to reconfigure this scaffolding to center structures that integrate holistic well-being and imagine alternate realities to healing. Our work contributes to the literature bringing structural competency to new spaces of clinical practice, contextualizing new frontiers for the exploration of chronic diseases across diverse clinical contexts worldwide.